PENGEMBANGAN MEDIA PEMBELAJARAN BERBASIS CANVA UNTUK MENINGKATKAN KREATIVITAS GURU DI SEKOLAH DASAR - Febriana, Tantri; Suneki, Sri; Suyoto, Suyoto; Rochajati, Siti (JURNAL SINEKTIK, 2024)
First of all, there are problems with instructors who do not provide a sufficient variety of learning media. Less interesting learning materials provide students with a more boring and uninspiring learning environment. This research aims to evaluate how learning media made with Canva can encourage teachers at SDN Karangrejo 01 to think more creatively. This research is a Research and Development (R&D) development using the 4D development model which consists of four stages which include define, design, develop and disseminate. A team consisting of media experts and content experts will assess this learning tool as it is being developed. The validation test results conducted by media experts revealed that creating Canva-based learning media was very feasible. The test yields a 91% percentage result. The percentage of material expert validation test results of 98% is within the range of very practical norms. It can be seen from the results of the validation test that Canva-based development media can be an application for teachers, so that teacher creativity increases